Pengaruh Penggunaan Bahan Bakar Pertamax 92 dan Akra 92 Terhadap Unjuk Kerja Motor Bensin 4 Langkah (Ichikawa PT-3700V, 163cc) - R Yudi Hartono; Aini Lostari (Universitas Muhammadiyah Ponorogo, 2018)
The use of fuel in the automotive world is very important because it can improve the performance of the fuel motor. Fuel with high octane numbers will be able to boost the performance of the fuel motor. The selection of the right fuel will also be a reference in the process of motor maintenance in the automotive world in Indonesia, now again being incessantly making creations and innovations. This research is to find out the power, torque, and average effective pressure (BMEP). The research method used is an experimental method using two fuels, namely Pertamax 92 and Akra 92. This needs to be done because both of these fuels have the same octane number as the performance test against the need to prove which one can be used for gasoline type vehicles. From the research results obtained the power, torque, and the firstx BMEP 92 are higher than the power, torque and BMEP akra 92.